Piezo1 and IFT88 synergistically regulate mandibular condylar chondrocyte differentiation under cyclic tensile strain. (June 2022) - Zhang, Zhuoyu; Sa, Guoliang; Wang, Zhuo; Wei, Zequan; Zheng, Liwu; Zhang, Ruochen; Zhu, Xinbiao; Yang, Xuewen
Abstract: Objective(s): Mandibular condyle chondrocytes (MCCs) are exposed to various mechanical environments. Primary cilia, as a carrier for ion channels, can sense mechanical signals. Intraflagellar transport protein 88 (IFT88) is crucial for the assembly and function of primary cilia. Piezo1 is a mechanically activated ion channel that mediates mechanical signal transduction. This study aimed to identify the possible synergistic effect between Piezo1 and IFT88 in MCC differentiation during mechanical conduction. Materials and methods: Confocal immunofluorescence staining was used to reveal the Piezo1 localization. Small interfering RNA (siRNA) technology was used to knock down the expression levels of Piezo1 and IFT88. The chondrogenic differentiation ability of MCCs was evaluated by Alcian blue staining, and the early differentiation ability was evaluated by Western blot of SOX9 and COL2A1. Results: Confocal immunofluorescence results showed that Piezo1 localized in the root of primary cilia. Without cyclic tensile strain (CTS) stimuli, Alcian blue staining showed that Piezo1 knockdown had a marginal effect on the chondrogenic differentiation of MCCs, while IFT88 knockdown inhibited the chondrogenic differentiation. The protein levels of SOX9 and COL2A1 decreased significantly with CTS stimuli. However, these protein levels were restored when Piezo1 was knocked down. In addition, IFT88 knockdown decreased the protein level of Piezo1 with or without CTS. Conclusion: Piezo1 and IFT88 might play a synergistic role in regulating MCC differentiation under CTS stimuli. Highlights: Piezo1 co-localized with primary cilia in mandibular condyle chondrocytes. Piezo1 inhibited early differentiation of mandibular condyle chondrocytes under cyclic tensile strain stimuli. Piezo1 was regulated by IFT88 in mandibular condyle chondrocytes under cyclic tensile strain stimuli.